Anatomy of leaves of Siberian species of the genus Lilium in conditions of Western Siberia forest zone - Tatiana N. Belaeva; Liu Si; Alina N. Butenkova; Alexey S. Prokopyev (Acta Biologica Sibirica)
Siberia harbors four lily species. The number of Siberian lily populations has declined in recent years due to habitat disturbance caused by anthropogenic impact, including tourism, urban expansion, economic activities, and active harvesting of flowering plants for bouquets. The aim of this study was to conduct a comparative analysis of the leaf anatomical structure of three Siberian species of the genus Lilium (L. pensylvanicum Ker-Gawler, L. pilosiusculum (Freyn) Miscz. and L. pumilum DC.), successfully introduced into the Siberian Botanical Garden of Tomsk State University, in order to identify their adaptive potential, including water stress tolerance and insolation in culture. The values of indicators from different species were compared by one-way analysis of variance (ANOVA). Reliable differences were revealed between the studied species in 13 quantitative parameters of the anatomical structures: the number and size of epidermal cells, leaf thickness, thickness of the lower and upper epidermis, mesophyll, columnar mesophyll, and the width of the cells of the upper mesophyll layer. In the conditions of the forest zone of Western Siberia, the studied species exhibit different water stress tolerance: from xerophyte L. pumilum to mesophyte L. pensylvanicum and more broad-leaved mesophyte L. pilosiusculum. Among the studied lilies, L. pumilum is a sun-loving plant, L. pilosiusculum is a shade-tolerant plant, and L. pensylvanicum occupies an intermediate position. This modern anatomical study of lilies in the forest zone of Western Siberia was conducted for the first time, which made it possible to obtain original quantitative characteristics of the epidermis and mesophyll of the leaf blades of plants brought into culture from natural habitats in Northern Asia.